2017
DOI: 10.1515/manment-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Green marketing today – a mix of trust, consumer participation and life cycle thinking

Abstract: SummaryA transition for a green, circular economy has encouraged companies to use new tools which boost sustainability. The purpose of this article is to discuss the consideration of life cycle thinking in green marketing as realized by companies. This theoretical-conceptual study aims to analyze life cycle assessment (LCA) as a useful tool for assessing green marketing goals. We also intend to highlight the importance of creating consumer trust for green business by displaying the green credentials of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
11
0
3
Order By: Relevance
“…To this end, it was necessary to find out what explicit and implicit preferences consumers have and reveal the relationships between their choices. Our goal was to clarify the issue of effective and easyto-understand eco-marketing communication, the creation of which, according to Lewandowska et al (2017), is still considered as a challenge. We agree with Mkhize and Ellis (2019), who say that in the case of sustainable and local foods, farmers and retailers aim to market the benefits of consuming organic products in a way that increases organic purchases but based on an analysis of available resources, we have found that there is no single recommendation on how this goal should be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, it was necessary to find out what explicit and implicit preferences consumers have and reveal the relationships between their choices. Our goal was to clarify the issue of effective and easyto-understand eco-marketing communication, the creation of which, according to Lewandowska et al (2017), is still considered as a challenge. We agree with Mkhize and Ellis (2019), who say that in the case of sustainable and local foods, farmers and retailers aim to market the benefits of consuming organic products in a way that increases organic purchases but based on an analysis of available resources, we have found that there is no single recommendation on how this goal should be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…According to Vilkaite-Vaitone and Skackauskiene (2019), the biggest benefits of environmental marketing communication include: strengthening customer relationships, increasing profits, achieving organizational goals, strengthening competitive advantage, reducing costs or improving brand reputation. According to Lewandowska et al (2017), however, creating effective and easy-to-understand eco-marketing communication can be a real challenge for manufacturers and retailers. Green marketing, in general, incorporates philosophy and a wide range of other activities to satisfy the needs and wishes of consumers and thus create a favorable position for the company by communicating its environmental, social and economic interests (Villarino and Font, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The favorable position of the company towards its competitors will allow it to exploit the advantages offered by the choice of a green brand positioning. C. By referring to the green product life-cycle, the following strategic alternatives are noted (Mera, 2003;Lewandowska et al, 2017):…”
Section: Marketing Communication Strategies For Green Brandsmentioning
confidence: 99%
“…▪ Communication without reference to the life-cycle of the product -involves highlighting the general green aspects of the company, which have no direct connection with the green quality of any stage of the life cycle of the product. Lewandowska et al (2017) considers that life cycle assessment for a green product is a good foundation for marketing campaigns. D. Depending on the desired change in consumer behavior, communication strategies can be (Danciu, 2006(Danciu, , 2012Ottman, 2011):…”
Section: Marketing Communication Strategies For Green Brandsmentioning
confidence: 99%
“…No obstante, con el transcurrir de los años, el marketing desarrolló una función social a través de la cual, se considera que debe permitir que la sociedad satisfaga sus necesidades y generar un impacto positivo en la vida de los seres humanos (Kotler y Levy, 1969). De acuerdo con Pérez (2004), el uso eficiente de los recursos no renovables, el cuidado y protección ambiental, la preocupación por las especies en peligro de extinción y el desarrollo sostenible se han constituido en un foco de interés para diversas instancias; dicha situación ha ocasionado que el consumidor del siglo XXI refleje una mayor preocupación por el cuidado del ecosistema y se incline por la adquisición de productos ecoamigables (Lewandowska, Witczak y Kurczewski, 2017).…”
Section: Introductionunclassified